The Belisana spiders (Araneae: Pholcidae) from Xishuangbanna Tropical Botanical Garden, Yunnan, China - Yao, Zhiyuan; Zhu, Keli; Du, Zhiheng; Li, Shuqiang (Zootaxa, 2018)
Five new species of the spider genus Belisana Thorell, 1898 are described based on material collected in the Xishuangbanna Tropical Botanical Garden (Yunnan, China). They are: B. dian Yao & Li sp. nov. (male), B. gupian Yao & Li sp. nov. (male, female), B. chenjini Yao & Li sp. nov. (male, female), B. xtbg Yao & Li sp. nov. (male, female), and B. yangxiaodongi Yao & Li sp. nov. (male, female). B. schwendingeri Huber, 2005 and B. zhengi Yao, Pham & Li, 2015 are reported from China for the first time. All material studied is deposited in the Institute of Zoology, Chinese Academy of Sciences (IZCAS) in Beijing, China.